2022
DOI: 10.1080/21655979.2022.2054500
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-486-5p functions as a diagnostic marker for carotid artery stenosis and prevents endothelial dysfunction through inhibiting inflammation and oxidative stress

Abstract: Carotid artery stenosis (CAS) can cause ischemic stroke, and clinical intervention for CAS is critical clinically. The purpose of this study was to explore the expression changes of microRNA-486-5p in the serum of patients with CAS and its possible mechanism. Ninety-one cases with asymptomatic CAS were recruited, and serum levels of miR-486-5p were measured using RT-qPCR. The diagnostic ability was evaluated by drawing the receiver operating characteristic (ROC) curve. Human aortic endothelial cells (HAECs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, previous reports characterized miR-155 and miR-122 as suppressors of cell migration and oxidative stress, including vascular SMC ( Tong et al, 2023 ), whereas knockdown of miR-155-5p results in increased proliferation and migration of human brain micro-vessel ECs ( Liu et al, 2015 ). Another significantly upregulated lncRNA, ENSMUST00000131663, had potential binding sites for miR-486-5p, which is known to function as a diagnostic marker for carotid artery stenosis and preventing endothelial dysfunction by inhibiting inflammation and oxidative stress ( Zhu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous reports characterized miR-155 and miR-122 as suppressors of cell migration and oxidative stress, including vascular SMC ( Tong et al, 2023 ), whereas knockdown of miR-155-5p results in increased proliferation and migration of human brain micro-vessel ECs ( Liu et al, 2015 ). Another significantly upregulated lncRNA, ENSMUST00000131663, had potential binding sites for miR-486-5p, which is known to function as a diagnostic marker for carotid artery stenosis and preventing endothelial dysfunction by inhibiting inflammation and oxidative stress ( Zhu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… 16 A recent animal study found that oxLDL treatment contributes to the inflammatory response and oxidative stress in human aortic endothelial cells, linking oxLDL and C‐reactive protein to atherosclerosis, endothelial dysfunction, oxidative stress, and inflammatory response from a molecular perspective. 28 However, the evidence on the association of combined oxLDL and hs‐CRP with poor prognosis after stroke is limited. In the current study, we used the upper quartile of oxLDL and hs‐CRP to differentiate between high and low risk, and found the association of oxLDL and hs‐CRP and adverse vascular outcomes appears only at both high levels, when both low levels treated as the reference group, which is in accord with other studies on the association of oxLDL and hs‐CRP with coronary events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the downregulation of miR-206, miR-9-5p, and miR-637 in the patients had predictive value for the incidence of cerebrovascular events within 5 years [ 181 , 182 , 183 ]. Interestingly, an in vitro proliferation assay indicated that overexpression of miR-503-5p significantly inhibited the proliferation of VSMCs, thus improving atherosclerosis [ 184 ] and that miR-486-5p prevented endothelial dysfunction in association with an anti-inflammatory and antioxidative effect by targeting the nuclear factor of activated T cells 5 (NFAT5) [ 185 ].…”
Section: Mirnas As Regulators Of Atherosclerosis and Ischemic Strokementioning
confidence: 99%